Parsing IPA Transcriptions with CLTS (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
The Cross-Linguistic Transcription Systems (CLTS, https://clts.clld.org) project serves as a reference catalogue for speech sounds. At the core of the project is a generative method that parses existing IPA transcriptions (or transcriptions in other supported transcription systems) and checks if they conform to the principles and components laid out in the reference catalogue. As a result, Cross-Linguistic Transcription Systems is much more than a simple list of possible speech sounds transcribed in the International Phonetic Alphabet, but a system that allows to generate possible speech sounds and to check if sounds provided in various transcription systems contain problems. This study gives a short overview on the basic ideas that lead to the creation of the database and the parsing method and provides some examples showing how it can be employed in practice.
Keywords: CLTS; IPA; phonetic transcription